T H E P R I VAT E F I N A N C E I N I T I AT I V E I N L O C A L GOVERNMENT - Rob Ball , David King (Published by Blackwell Publishing, Oxford, 2006)
This paper distinguishes between the Private Finance Initiative (PFI) and the more general Public Private Partnerships (PPP). It traces the growth of the initiative since its start in 1992 to the current day and considers the implications of PFI for the public finances. A number of economic issues are discussed including bidding costs, financing costs and whole life costing. The importance of risk transfer in the value for money analysis of PFI projects is emphasised and the extent to which risk actually is transferred is questioned. Finally, the contribution of PFI towards modernising public service is recognised but the Audit Commission’s recommendation that a wider range of procurement tools ought to be considered is noted